Optimization of Medical Equipment Inventory Management Through Barcode-Based Digitalization - Maria Indah Septirini; Tuti Afriani; La Ode Abdul Rahman; Krisna Yetti; Dyah Fitri Wulandari (GLOBAL HEALTH SCIENCE GROUP, 2026)
Digital transformation in medical equipment logistics is a vital part of healthcare reform, aiming to enhance efficiency, accuracy, and patient safety. One of the main challenges at hospital is the manual documentation system for borrowing and returning medical equipment, which results in low accountability, service delays, and a high risk of equipment loss. : Case report area focused on the HCU/PICU unit. This study aims to describe the implementation process of a barcode-based digital medical inventory system through a managerial approach and planned change intervention based on Kurt Lewin's theory. A case report was conducted using Kurt Lewin’s planned change approach (unfreezing, moving, and refreezing), data analysis through observation, questionnaires, interviews, and implementation evaluation. The Assessment of Medical Equipment Management (MEM) questionnaire administered to 103 nurses revealed that 87.4% of units still use manual recording and 50.98% reported suboptimal coordination in equipment returns, with reliability 0.86 and validity loading factor ±0.5; content validity 85%. The intervention involved developing Standard Operating Procedures (SOPs) and technical guidelines for the